Stress Hematopoiesis Is Regulated by the Krüppel‐Like Transcription Factor ZBP‐89. (March 2014) - Li, Xiangen; Romain, Rachael D.; Park, Dongsu; Scadden, David T.; Merchant, Juanita L.; Arnaout, M. Amin
Abstract Previous studies have shown that ZBP‐89 (Zfp148) plays a critical role in erythroid lineage development, with its loss at the embryonic stage causing lethal anemia and thrombocytopenia. Its role in adult hematopoiesis has not been described. We now show that conditional deletion of ZBP‐89 in adult mouse hematopoietic stem/progenitor cells (HSPC) causes anemia and thrombocytopenia that are transient in the steady state, but readily uncovered following chemically induced erythro/megakaryopoietic stress. Unexpectedly, stress induced by bone marrow transplantation of ZBP89−/− HSPC also resulted in a myeloid‐to‐B lymphoid lineage switch in bone marrow recipients. The erythroid and myeloid/B lymphoid lineage anomalies in ZBP89−/− HSPC are reproduced in vitro in the ZBP‐89‐silenced multipotent hematopoietic cell line FDCP‐Mix A4, and are associated with the upregulation of PU.1 and downregulation of SCL/Tal1 and GATA‐1 in ZBP89‐deficient cells. Chromatin immunoprecipitation and luciferase reporter assays show that ZBP‐89 is a direct repressor of PU.1 and activator of SCL/Tal1 and GATA‐1. These data identify an important role for ZBP‐89 in regulating stress hematopoiesis in adult mouse bone marrow. Stem Cells2014;32:791–801